Modulation of local and systemic immune responses in brown trout (Salmo trutta) following exposure to Myxobolus cerebralis. Issue 106 (November 2020) - Saleh, Mona; Friedl, Adina; Srivastava, Mitaly; Secombes, Christopher J.; El-Matbouli, Mansour
Abstract: Myxobolus cerebralis, the etiological agent of Whirling Disease (WD), is a freshwater myxozoan parasite with considerable economic and ecological relevance for salmonids. There are differences in disease susceptibility between species and strains of salmonids. Recently, we have reported that the suppressor of cytokine signaling SOCS1 and SOCS3 are key in modulating rainbow trout ( Oncorhynchus mykiss ) immune responses and that resistant fish apparently exhibit effective Th17 cell response after exposure to M. cerebralis . It is unclear whether such molecules and pathways are also involved in the immune response of M. cerebralis infected brown trout ( Salmo trutta ). Hence, this study aimed to explore their role during immune modulation in infected brown trout, which is considered resistant to this parasite. Fish were exposed to the triactinomyxon (TAM) stages of M. cerebralis and quantitative real-time PCR (RT-qPCR) was carried out to examine local (caudal fin) and systemic (head kidney, spleen) immune transcriptional changes associated with WD over time in infected and control fish. All of the immune genes in the three tissues studied were differentially expressed in infected fish at multiple time points. Brown trout reduced the parasite load and demonstrated effective immune responses, likely by keeping pro-inflammatory and anti-inflammatory cytokines in balance whilst stimulating efficient Th17-mediated immunity. This study increases knowledge on the brown trout immune response to M. cerebralis and helps us to understand the underlying mechanisms of WD resistance. Highlights: Myxobulus cerebralis induces the expression of IFN-γ and IL-1β in brown trout. The anti-inflammatory gene expression of SOCS1, SOCS3 and TGF-β1b was induced. Infected brown trout exhibited elevated levels of Th17-associated cytokines. The brown trout Th17-mediated immune response may contribute to their resistance.